A rare case of breast carcinoma metastasis into a meningioma in a 64-year-old female patient - Edwin Mogere, MBChB, MMed; Miriam Mutebi, MBChB, MMed; Allan Njau, MBChB, MMed; Manel Haj Mansour, MD, MMed; Joseph Abuodha, MBChB, MMed; Patricia Okiro, MBChB, MMed (Radiology Case Reports, 2024)
This report discusses the occurrence of tumor-to-tumor metastasis—an atypical phenomenon in oncology where a secondary malignancy develops within an existing primary tumor. The case of a 64-year-old woman is presented, who, with a history of stage II invasive ductal carcinoma of the breast treated with mastectomy and chemoradiotherapy, developed neurological symptoms indicative of a secondary brain tumor. MRI and subsequent histopathological analysis post-craniotomy confirmed a meningioma with a metastatic breast carcinoma, demonstrating the clinical importance of considering tumor-to-tumor metastasis in similar patient histories.